PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH PADA PTSOXAL BATAMINDO INDUSTRIAL GASES - Fatimah, Ayu; Yusran, Rio Rahmat (EDUTECH CONSULTANT, 2020)
In manufacturing companies, cost is the main factor that must be considered to achieve maximum profit. This study aims to determine the effect of production costs and operational costs on net profit at PT Soxal Batamindo Industrial Gases. The sample in this study is the income statement. The method used in this study is a quantitative descriptive study that uses data in the form of figures obtained from the income statement for the period 2015 to 2018 at PT Soxal Batamindo Industrial Gases engaged in the oil and gas manufacturing industry. The population in this study includes production costs, operational costs and net income for the period 2015 to 2018. This study uses multiple linear data analysis techniques. The researcher uses SPSSapplication (Statistical Product and Service Solution) version 25to help in analyzing data. The results of the study stated that partially the production costs have a positive relationship and have a significant effect, while operational costs have a negative and not significant effect. Simultaneously the variable production costs and operational costs have a significant effect on PT Soxal Batamindo Industrial Gases.